Growth of Black Phosphorus Nanobelts and Microbelts. Issue 1 (24th November 2017) - Li, Jun; Gao, Zhaoshun; Ke, Xiaoxing; Lv, Yangyang; Zhang, Huili; Chen, Wei; Tian, Wanghao; Sun, Hancong; Jiang, Sai; Zhou, Xianjing; Zuo, Tingting; Xiao, Liye; et al.
Abstract: Black phosphorus nanobelts are fabricated with a one‐step solid–liquid–solid reaction method under ambient pressure, where red phosphorus is used as the precursor instead of white phosphorus. The thickness of the as‐fabricated nanobelts ranges from micrometers to tens of nanometers as studied by scanning electron microscopy. Energy dispersive X‐ray spectroscopy and X‐ray diffraction indicate that the nanobelts have the composition and the structure of black phosphorus, transmission electron microscopy reveals a typical layered structure stacked along the b ‐axis, and scanning transmission electron microscopy with energy dispersive X‐ray spectroscopy analysis demonstrates the doping of bismuth into the black phosphorus structure. The nanobelt can be directly measured in scanning tunneling microscopy in ambient conditions. Abstract : Black phosphorus micro‐ and nanobelts are fabricated with a novel method under ambient pressure from red phosphorus. The black phosphorus reveals a typical layered structure stacked along the b ‐axis with thickness ranges from micrometers to tens of nanometers, and can be directly measured in scanning tunneling microscopy in ambient conditions, owing to doping of bismuth.